The yucky reptile alphabet book - Pallotta, Jerry; Masiello, Ralph (Watertown, MA : Charlesbridge Pub., 1989)
An alphabet book depicting various reptiles.
4.9
K-3
Keywords: English language -- Alphabet -- Juvenile literature; Reptiles -- Juvenile literature; Alphabet; Reptiles; Alphabet; Reptiles